Corporate governance in the US and global settings - Ferris, Stephen P.; John, Kose.; Makhija, Anil K. (Bingley, U.K. : Emerald, 2014)
Volume 17 of Advances in financial economics, entitled "Corporate governance in the US and global settings" will provide further insights into corporate governance in the US & global economic and financial environment by publishing international, within-country and cross-country comparative studies. The volume will be edited by the series editors, Kose John, New York University, Anil Makhija, Ohio State University, and Stephen P. Ferris, University of Missouri.
Capital structure changes around cross-listings / Min-Yu (Stella) Liao, Chris Tamm -- Bridging the cultural divide : the role of foreign directors in cross-border mergers / Yaqoub Alabdullah, Stephen P. Ferris -- The impact of board diversity on corporate performance : new evidence from Southeast Europe / Filip Fidanoski, Kiril Simeonovski, Vesna Mateska -- Are CEOs myopic? A dynamic model of the ongoing debate / Moren Levesque ... [et al.] -- Introduction of equity-based compensation and impact on firm policies / Ranjan D'Mello, Mercedes Miranda -- Mergers and target transparency / Iftekhar Hasan ... [et al.] -- Institutional investors trading behavior in mergers and acquisitions / Rasha Ashraf, Narayanan Jayaraman.
Print version record
Keywords: Economics; Corporate finance; Corporate governance; Corporations